Synthesis, characterization, DNA-binding and biological activity of Zn(II) complexes of sulfadiazine with different amino acids - El-Henawy, Ahmed Abdlmonem; Hanafy, Ahmed Imam (European Journal of Chemistry, 2015)
New Zn(II) complexes (ZnII-VS, ZnII-LS, ZnII-SS, ZnII-CS and ZnII-MS) of the sulfonamide antibiotic sulfadiazine with different amino acids were prepared and fully characterized by elemental analyses, thermal analysis and IR, UV/Vis and 1H NMR spectroscopy. The IR and 1H NMR spectral data show that the ligands behave in a dibasic bidentate fashion coordinating to zinc ion. Interactions of these complexes with DNA were investigated by spectrophotometric method. Moreover, the antibacterial and antifungal activities were evaluated for five ligands and their complexes. The computational study for prediction of absorption, distribution, metabolism, elimination and toxic factors (ADMET) properties were performed for the prepared ligands.